THE IMPLEMENTATION OF ENHANCING MALE PARTICIPATION ON FAMILY PLANNING POLICY IN BANDUNG BARAT REGENCY - Suhenda, Dadang; Hutasoit, Evalina Franciska (Journal of Indonesian Health Policy and Administration, 2020)
This study aims to analyze the conduct implementation of the increasing male contraception policy in Bandung Barat Regency. The study is using qualitative methods with case studies approachment. Qualitative data were gained from 16 informants which consist of implementor group as program managers, and partnership and community group as the targeted group. This study was conducted at three locations: district of Cililin, Batu Jajar, and Parongpong. The study shows that the decision process to decide PPM as the standard and goals of the family planning program has been understood by all of its administrators and resources available for this program has been considered as sufficient in terms of quantity but yet still lack in quality. Furthermore, communication and coordination processes among administrators and associates are shown to be in accordance with the operational procedures, hence, influencing characteristics of the family planning programs. It is found that religion consideration makes the residents refuse male contraception. Family planning programs are considered as women's business for some certain people. Fortunately, the existence of a spirit of militancy, high loyalty and disposition/attitude possessed by the management officers towards this male family planning program has a major influence on the success of the program. Moreover, the study shows that politicians have demonstrated strong support for the family planning program. This supports take places through budgeting and politician's active participation in the male contraceptive programs